2020
DOI: 10.3390/ijerph17145178
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Link between Different Types of Alcoholic Drinks and Obesity? An Analysis of 280,183 UK Biobank Participants

Abstract: Understanding the associations between types of alcoholic drinks and adiposity has public health relevance, considering that adult overweight and obesity prevalence are increasing worldwide. We aimed to evaluate the association between overall alcohol consumption and types of alcohol drinks with markers of adiposity from the UK Biobank baseline data (n = 280,183, 48.3% female). Generalized linear models were used to examine the associations between alcohol consumption with body mass index (BMI) and body fat pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 46 publications
0
25
1
Order By: Relevance
“…3 Unemployed/Retired includes "never employed" (n = 3, 0.9%), "not employed but looking" (n = 25, 7.4%), and "retired" (n = 72, 21.3%). 4 Some College or less includes "Less than a high school education" (n = 1, 0.3%), "High school education or GED" (n = 30, 8.9%), "some college/no degree" (n = 64, 18.9%), and "Associate's degree" (n = 36, 10.7%). 5 Post-Graduate Degree includes "Master's degree" (n = 62, 18.3%), "Professional degree" (e.g., MD, DDS, etc.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3 Unemployed/Retired includes "never employed" (n = 3, 0.9%), "not employed but looking" (n = 25, 7.4%), and "retired" (n = 72, 21.3%). 4 Some College or less includes "Less than a high school education" (n = 1, 0.3%), "High school education or GED" (n = 30, 8.9%), "some college/no degree" (n = 64, 18.9%), and "Associate's degree" (n = 36, 10.7%). 5 Post-Graduate Degree includes "Master's degree" (n = 62, 18.3%), "Professional degree" (e.g., MD, DDS, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…3 Sum of winsorized values for vigorous, moderate, and walking PA hours per week. 4 Physical activity volume is based on weighted energy expenditure at each intensity level in MET hours per week [37]. 5 Sum of winsorized values for vigorous and moderate MET hours per week.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inan-Eroglu et al [ 78 ] examined the associations between types of alcoholic drinks and adiposity in a large United Kingdom cohort ( n = 280,183, 48.3% female). Study data indicated that when compared to non-wine drinkers, red wine, champagne, and fortified wine drinkers had lower BMIs (differences were as follows: −0.75 kg/m 2 , CI: −0.78, −0.72 kg/m 2 ; −0.48 kg/m 2 , CI: −0.52, −0.45 kg/m 2 ; and −0.24 kg/m 2 , CI: −0.29, −0.18 kg/m 2 , respectively).…”
Section: The Effects Of Wine/rsv On Obesitymentioning
confidence: 99%